Business process for architectural design brief - an industrial perspective - Abdullah Sani Ahmad, 1961-; Nurdina Mohd. Nor; Abd. Hakim Mohamed; Management in Construction Research Association (2004 : Kedah) (Skudai : Universiti Teknologi Malaysia, 2004)
02